DEVELOPMENT OF INFORMATION TECHNOLOGY AND COMMUNICATION MEDIA IN EDUCATION - Sriwati Sriwati; Rifqi Zaeni Achmad Syam (Jurnal Scientia, 2023)
The development of information and communication technology has not been matched by an increase in human resources which determines the success of the world of education in Indonesia. This is because the human resources are still lagging behind to utilize information technology in the educational process. Information and communication technology itself is a multimedia-based learning system (text, image, sound and video) that is able to make the presentation of a topic interesting, not monotonous and easy to digest. This research was conducted to find out how the application of information and communication technology in assisting the learning process between students and teachers. This aims to determine the effectiveness of the learning process which is not carried out face-to-face, but can use other communication media which are applied through information and communication technology which can also develop the creativity of students and teachers in finding broader learning materials. The method used in this writing is literature study, in this literature study the authors use various written sources such as articles, journals, books, and relevant documents in accordance with this writing. The results of this writing show that in terms of learning activities that apply Information and Communication Technology Media it makes students more interested and enthusiastic in delivering learning material, so that they can achieve the principles of active, innovative, creative and effective learning.